Iron Dyshomeostasis and Ferroptosis: A New Alzheimer’s Disease Hypothesis? - Wang, Feixue; Wang, Jiandong; Shen, Ying; Li, Hao; Rausch, Wolf-Dieter; Huang, Xiaobo (Frontiers in Aging Neuroscience, 2022)
Iron plays a crucial role in many physiological processes of the human body, but iron is continuously deposited in the brain as we age. Early studies found iron overload is directly proportional to cognitive decline in Alzheimer’s disease (AD). Amyloid precursor protein (APP) and tau protein, both of which are related to the AD pathogenesis, are associated with brain iron metabolism. A variety of iron metabolism-related proteins have been found to be abnormally expressed in the brains of AD patients and mouse models, resulting in iron deposition and promoting AD progression. Amyloid β (Aβ) and hyperphosphorylated tau, two pathological hallmarks of AD, can also promote iron deposition in the brain, forming a vicious cycle of AD development-iron deposition. Iron deposition and the subsequent ferroptosis was found to be a potential mechanism underlying neuronal loss in many neurodegenerative diseases. Iron chelators, antioxidants and hepcidin were found useful for treating AD, which represents an important direction for AD treatment research and drug development in the future. The review explored the deep connection between iron dysregulation and AD pathogenesis, discussed the potential of new hypothesis related to iron dyshomeostasis and ferroptosis, and summarized the therapeutics capable of targeting iron, with the expectation to draw more attention of iron dysregulation and corresponding drug development.